Study of the Catalytic Activity and Surface Properties of Manganese-Zinc Ferrite Prepared from Used Batteries - Katarzyna Winiarska; Roman Klimkiewicz; Włodzimierz Tylus; Agnieszka Sobianowska-Turek; Juliusz Winiarski; Bogdan Szczygieł; Irena Szczygieł (Journal of Chemistry)
The catalytic activity of the Mn-Zn ferrites obtained by chemical methods from a solution after acid leaching of waste Zn-C and Zn-Mn batteries was studied. Precursors of metal ions (Fe, Mn, and Zn) were obtained using different precipitating agents ((NH4)2C2O4, Na2CO3, and NaOH), and then, the combustion route was used to prepare catalytically active nanocrystalline ferrites. The obtained ferrite catalysts differ in terms of microstructure, the number of acid and base sites, and the surface composition depending on the ion precursor used in the combustion process. All prepared materials were catalytically active in the butan-1-ol conversion test. Depending on the ion precursor applied in the combustion process, a selective catalyst towards aldehyde (carbonate precursor) or ketone (hydroxide precursor) formation can be obtained. Furthermore, the catalyst prepared from the hydroxide precursor exhibits the highest catalytic activity in the n-butanol test (nearly 100% conversion under the experiment conditions).